Perubahan Paradigma Studi Agama pada Program Studi Perbandingan Agama Universitas Islam Negeri (UIN) Sunan Ampel, Surabaya - Hamdi, Ahmad Zainul (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2015)
This article is aimed to assess the progress of Islamic and religious studies at State Islamic University (UIN) Sunan Ampel Surabaya throughout the view of new paradigm on Islamic studies. It attempts to seek whether there is a shifting paradigm from parochial Islamic studies to dialogical Islamic studies that could accommodate contemporary social scientific instruments. It is based on one core question, “is the Islamic studies at UIN Sunan Ampel—especially the Department of Comparative Study of Religions—still based on normative-doctrinal studies or based on historical critics?” This paper took four undergraduate theses as a sample, starting from 2011 back to forty years before. Each thesis represents one-decade period. In order to analyze religious studies at the Department of Comparative Study of Religions will be a strategic stage to observe methodological perspective, namely insider-outsider perspective. Having examined all of these theses, this article concludes that Islamic religious studies at the Department of Comparative Study of Religions have not changed at all. It shows signs of stagnating after four decade of teaching religious studies in this department.